2019
DOI: 10.1038/s41598-019-44578-5
|View full text |Cite
|
Sign up to set email alerts
|

Combination of TLR2 and TLR3 agonists derepress infectious bursal disease virus vaccine-induced immunosuppression in the chicken

Abstract: Live intermediate plus infectious bursal disease virus (IBDV) vaccines (hot vaccines) are used for protection against the virulent IBDV strains in young chickens. We evaluated the potential of Toll-like receptor (TLR) agonists to alleviate hot vaccine-induced immunosuppression. The combination of Pam3CSK4 and poly I:C synergistically upregulated IFN-β , IFN-γ , IL-12 , IL-4 , and IL-13 transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 82 publications
2
4
0
Order By: Relevance
“…Interestingly, we observed that some molecules of the antiviral pathway were stronger activated in the B87 group at 4 hpi, while others were not; however, the activation of macrophages and the Th1/Th2 ratio were not different between the two groups at this time point. Further, as compared to the HLJ0504-like vvIBDV group, the antiviral signaling, macrophage activation and cytokine expression in the B87 group were far more moderated during the early infection stage, consistent with the research from the earlier reports [18,19,60] in the bursa, suggesting that the activation of the antiviral response in the B87 group at 4 hpi might be transient and then downregulated which might be related to the easier dissemination of B87 and consistent with the biology of this vaccine strain.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, we observed that some molecules of the antiviral pathway were stronger activated in the B87 group at 4 hpi, while others were not; however, the activation of macrophages and the Th1/Th2 ratio were not different between the two groups at this time point. Further, as compared to the HLJ0504-like vvIBDV group, the antiviral signaling, macrophage activation and cytokine expression in the B87 group were far more moderated during the early infection stage, consistent with the research from the earlier reports [18,19,60] in the bursa, suggesting that the activation of the antiviral response in the B87 group at 4 hpi might be transient and then downregulated which might be related to the easier dissemination of B87 and consistent with the biology of this vaccine strain.…”
Section: Discussionsupporting
confidence: 87%
“…The severity of lesions was more evident on 14th and 21st day PI. In corroboration to our findings, other researchers have also observed mild to severe changes with vacuolation and depletion of lymphoid cell in bursal follicles 27 , 30 32 . Immunosuppressive nature of intermediate plus vaccine due to severe lesions in BF of vaccinated chickens have also been reported by other researchers 13 , 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Bashir et al (2019) reported the use of a combination of TLR agonists, including pam3CSK4 (TLR2 agonist) and poly I:C (TLR3 agonist), as an effective strategy to alleviate virus-induced immune suppression associated with the use of live attenuated infectious bursal disease vaccines (hot vaccines that may induce immune suppression) in chickens. This reduced immune suppression is attributed to the upregulation of IFN-β, IFN-γ, IL-12, and IL-4, and inhibition of IL-1β, IL-10, and inducible nitric oxide synthases (iNOS) expression through the synergistic effect of both TLR ligands [ 51 ]. Interestingly, in our studies, the group of embryos treated with CpG ODN 10 µg (half of the stand-alone dosage) in combination with 15 µg of poly I:C/embryo showed 100% survival in the first 7 days post-challenge ( Figure 2 b), whereas the stand-alone treatment of CpG ODN at 10 µg or poly I:C at 10 or 20 µg per embryo was not as effective as the combination.…”
Section: Discussionmentioning
confidence: 99%